Interaction with Protein Phosphatase 1 Is Essential for bifocal Function during the Morphogenesis of the Drosophila Compound Eye - Helps, Nicholas R. (American Society for Microbiology, 2001)
The gene bifocal (bif), required for photoreceptor morphogenesis in the Drosophila compound eye, encodes a protein that is shown to interact with protein phosphatase 1 (PP1) using the yeast two-hybrid system. Complex formation between Bif and PP1 is supported by coprecipitation of the two proteins. Residues 992 to 995 (RVQF) in the carboxy-terminal region of Bif, which conform to the consensus PP1-binding motif, are shown to be essential for the interaction of Bif with PP1. The interaction of PP1 with bacterially expressed and endogenous Bif can be disrupted by a synthetic peptide known to block interaction of other regulatory subunits with PP1. Null bif mutants exhibit a rough eye phenotype, disorganized rhabdomeres (light-gathering rhodopsin-rich microvillar membrane structures in the photoreceptor cells) and alterations in the actin cytoskeleton. Expression of wild-type bif transgenes resulted in significant rescue of these abnormalities. In contrast, expression of transgenes encoding the Bif F995A mutant, which disrupts binding to PP1, was unable to rescue any aspect of the bif phenotype. The results indicate that the PP1-Bif interaction is critical for the rescue and that a major function of Bif is to target PP1c to a specific subcellular location. The role of the PP1-Bif complex in modulating the organization of the actin cytoskeleton underlying the rhabdomeres is discussed.